Approaches to Teaching English Pronunciation - Kiacová, Veronika (Univerzita Pardubice, 2023)
This thesis deals with the approaches of upper-secondary school teachers to teaching English pronunciation. The theoretical part presents significant past and present approaches to teaching pronunciation. Furthermore, the theoretical part presents the main aim of pronunciation and relevant didactic procedures for teaching pronunciation and defines the classification of upper-secondary schools. Finally, in the practical part, the research aimed to find out how English language teachers at upper-secondary schools approach teaching pronunciation is presented. Collecting and analysing the data procedure is demonstrated here, and the research results are presented.
Přístupy vyučujících k výuce výslovnosti v hodinách angličtiny
Keywords: přístupy; vyučující; výuka výslovnosti; vyšší sekundární vzdělávání; approaches; teachers; teaching pronunciation; upper-secondary education